DECISION SUPPORT SYSTEM TO ELECT THE BEST USTADZ USING SIMPLE ADDITIVE WEIGHTING METHOD - Muhammad Abdan Syakuro; Desti Fitriati (Kresnamedia Publisher, 2021)
Pesantren is a place for students to live and learn religious education. In Pesantren there are human resources that very helpful for learning in boarding school, namely ustadz. In the process of successful education, sometimes pesantren needs to make an assessment to improve the quality of education, one of it is conducting the best selection of ustadz adequate and exceeding the average. The number of ustadz that exist causes difficult decision making of the best ustadz elections quickly, accurately and has not been able to give maximum results and takes a very long time in calculation. In addition, the selection of the best ustadz in Pesantren Qur'an Al Hikmah Bogor is still not objective because the selection of the best ustadz is still appointed directly without using calculations. Based on the problems described above, a Decision Support System (DSS) application is needed using simple additive weighting method to help in making the best ustadz decision in pesantren. This system is a dynamic system where users can set the parameters of criteria and weights themselves. Besides, From the making of the Decision Support System produced accuracy of 90% of 30 samples according to which are 27 samples.